Gambaran Gejala Kecemasan dan Halusinasi Auditorik Pada Pasien ODGJ: Studi Observasi di Pusat Rehabilitasi Welas Asih Indonesia Waras Ministry Walantaka - Isyana Nurul Ainiah Ana; Yahdinil Firda Nadirah (STKIP Subang, 2025)
This study aims to identify and analyze the manifestation of anxiety and auditory hallucination symptoms experienced by a patient with Severe Mental Illness (ODGJ) undergoing treatment at the Welas Asih Indonesia Waras Ministry Rehabilitation Center. This research uses a qualitative descriptive case study method, with Mr. Santono, a patient with a history of anxiety and hallucinations for one year, as the main subject. Data was collected through in-depth observation of the subject's behavior and reinforced by interviews with the patient's companion. The results show that the subject still experiences significant residual symptoms, manifested as social withdrawal (avoidance) and auditory hallucinations (hearing whispers) that are commanding and blaming. Theoretically, these symptoms are consistent with anxiety disorder and a dysfunction of reality perception, leading to distress, loss of self-control, as well as impaired adaptive and social functions. Nevertheless, the integrated spiritual and psychosocial rehabilitation approach proved effective in stabilizing the subject's emotional condition and reducing the intensity of the symptoms.